Comparison of novel native probiotics and paraprobiotics in modulating oxidative stress and inflammation in DSS-induced colitis: implications for enhanced therapeutic strategies in high fat diet - Niloofar Rezaie; Shadi Aghamohammad; Elham Haj Agha Gholizadeh Khiavi; Mohammad Reza Pourshafie; Malihe Talebi; Mahdi Rohani (BMC Immunology)
Abstract Aim IBD is a condition that may result from the presence of oxidative stress. The objective of this research is to evaluate and compare the potency of probiotics and paraprobiotics to modulate oxidative stress and inflammation. Methods and results In the initial phase, the antioxidant capabilities of 88 strains from Lactobacillus and Bifidobacterium were evaluated. In the subsequent phase, during the in-vivo stage, four experimental groups were established, consisting of a high-fat diet (HFD) + PBS, HFD + DSS, HFD + DSS + 10^9 cfu/ml of 6 selected native probiotic, and HFD + DSS + 10^9 cfu/ml of paraprobiotic (from 6 selected strains), with male wild-type C57BL/6 mice being assigned to these groups. The phenotypical indices and pathological scores along with the evaluation of the expression of genes associated with the NF-kB and Nrf2 signaling pathways, as well as enzymes linked to oxidant/anti-oxidant activities, and proinflammatory/inflammatory cytokines were performed. A significant difference was noted among the groups exposed to DSS and groups that given our native agents. The mice receiving a blend of probiotics and paraprobiotics alongside DSS demonstrated a mitigation of the harmful impacts caused by DSS, both regarding phenotypic traits, including pathological scores and also the level of cytokines and antioxidant markers and also molecular indicators like the Nrf2 and NF-kB associated genes. Also, there was no notable difference between our native probiotic and paraprobiotic. Conclusion The study’s findings provide evidence that the expression of inflammation can be successfully alleviated by utilizing our native probiotics and paraprobiotics, with a greater emphasis on the latter due to its inherent safety. Impact statements This study highlighted the anti-inflammatory and antioxidant properties of probiotic and paraprobiotic that could be useful for patients with inflammatory status.